Effects of 2, 2-Dithiodipyridine as a Leveler for Through-Holes Filling by Copper Electroplating. Issue 13 (1st January 2019) - Wang, Xu; Zhang, Shengtao; Chen, Shijin; Tan, Bochuan; Guo, Hailiang; Wang, Ya; Qiang, Yujie; Fu, Shulei; Wen, Yanan
Abstract : 2, 2-dithiodipyridine (DTDP), a low molecular weight nitrogen-containing heterocyclic compound with a disulfide bond, is added as a novel leveler to the plating solution to achieve the void-free filling of through-holes (THs) by butterfly technology (BFT). Herein, quantum chemical calculation and molecular dynamics (MD) simulation theoretically manifest that DTDP can adsorb on the copper surface through its plentiful active sites and strong adsorption capacity, which can provide theoretical support for DTDP as a leveler. Not only that, the test results of scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) and electrochemical measurements further confirm that DTDP can form an adsorption film on the copper surface, which not only improves the surface morphology of copper, but also increases the cathodic polarization, resulting in the inhibition of copper deposition. Remarkably, under the synergistic effects of various additives, the perfect filling performance of THs can be achieved by adding a proper concentration of DTDP to the electroplating solution. Combined with all the test results, the conjecture of DTDP as a potential leveler of THs filling by copper electroplating is confirmed.